Water Hyacinth and Education Research Trends from The Scopus Database: A Bibliometric Literature Review - Siti Nur Hofifah; Asep Bayu Dani Nandiyanto (ASEAN Journal of Science and Engineering Education, 2024)
This study aims to visualize data, trace the research trends, and evaluate research on water hyacinths and education from 2010 to 2023. This research used a database from Scopus. The data search used the keywords water hyacinth education and water hyacinth. We got 953 data articles and review articles. The data was then analyzed using Ms. Excel to analyze the number of articles, the number of citations per year, and the highest number of citations. The data was then mapped using the VOSviewer software. The mapping results were analyzed to see research trends based on related keywords. The results of the data visualization show that there are 374 keyword items grouped into 4 clusters. The results of taking data from 2010 to 2023 show that the research trend of water hyacinth and education tends to increase. Nonetheless, we evaluate that more research on water hyacinth is carried out in the fields of pure scientific research such as ecological communities, socio-economic effects, reproduction, its potential as bioenergy, and physiochemical properties. Thus, water hyacinth research opportunities in the field of education still have very broad potential to be carried out. This study was expected to provide information on research trends, mapping, and evaluation of research on water hyacinths and education.